Analisis Standarisasi Depot Air Minum Isi Ulang (DAMIU) di Kabupaten Pelalawan Tahun 2021 – 2022 - Jamaluddin, Jamaluddin; Anasthasia, Yanisa (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
This research aims to determine the quality of drinking water at refilled drinking water depots (DAMIU) in Pelalawan Regency in 2021-2022. This type of research is quantitative descriptive research. Testing of the data that has been obtained is done with the help of a statistical application, namely the SPSS version 25 application. The research results show that in 2021, there will be 200 depots carrying out environmental health inspection (IKL) activities and examining drinking water depot water samples. Data that has proper hygiene sanitation is only 97 depots and only 38 depots have received certificates worthy of sanitation hygiene (SLHS). Meanwhile, in 2022 the number of existing water depots will be 135 depots, of this number only 64 depots will carry out environmental health inspection (IKL) activities and examine drinking water depot water samples. 42 DAMIU depots have proper hygiene and sanitation and have obtained SLHS or meet the requirements. Some DAMIUs do not yet have an operational permit. So, it can have fatal consequences for the health of people who use water from DAMIU production.